2010
DOI: 10.1590/s0100-67622010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Correlações da altura e diâmetro com tensões de crescimento em árvores de Corymbia citriodora e Eucalyptus urophylla

Abstract: RESUMO -O uso múltiplo das florestas plantadas pelo setor industrial de base florestal vem aumentando gradativamente. Hoje, a utilização da madeira de eucalipto para fins mais nobres já é uma realidade. Porém, algumas limitações como a presença de tensões de crescimento são responsáveis por grandes perdas no setor. As tensões de crescimento geram rachaduras de topo em toras e tábuas e também empenamentos nas peças após o desdobro. Dentro desse contexto, este trabalho objetivou avaliar essas tensões em diferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
2
4
0
8
Order By: Relevance
“…Regarding the functional relation between DBH and LRS, Valencia et al (2011) reported that the processing of wood logs from old trees tends to present a decrease in the issues from the growth stresses due to their larger diameter, because the stresses are distributed in a larger radius. As found in the present study, Carvalho et al (2010) found positive and significant correlation between LRS and DBH for trees from Eucalyptus urophylla and Corymbia citriodora, both analyzed at 13 years old. This influence of the DBH on the LRS for trees from Corymbia citriodora and Eucalyptus urophylla was also found by Gonçalves (2007), analyzing 15 years old trees.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding the functional relation between DBH and LRS, Valencia et al (2011) reported that the processing of wood logs from old trees tends to present a decrease in the issues from the growth stresses due to their larger diameter, because the stresses are distributed in a larger radius. As found in the present study, Carvalho et al (2010) found positive and significant correlation between LRS and DBH for trees from Eucalyptus urophylla and Corymbia citriodora, both analyzed at 13 years old. This influence of the DBH on the LRS for trees from Corymbia citriodora and Eucalyptus urophylla was also found by Gonçalves (2007), analyzing 15 years old trees.…”
Section: Discussionsupporting
confidence: 88%
“…ages, according to LIMA et al, 2004;BOTREL et al, 2007;CARVALHO et al, 2010;BELTRAME et al, 2012. These comparisons indicated that the development of the trees from this study occurred under suitable edafoclimatic conditions, which confer a normal physiological activity to them (YANG et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Valencia et al (2011) também verificaram em uma população de E. nitens, de 22 anos, que a DRL não tem relação com o diâmetro das árvores. Entretanto, Carvalho et al (2010) verificaram que a DRL tem correlação com as classes de DAP, sendo que as mesmas mostraram-se negativas e significativas; dessarte, para esses autores, a classe de DAP é um parâmetro a ser utilizado em seleções de indivíduos, com menores intensidades de tensões de crescimento tanto em populações de Corymbia citriodora como de E. urophylla.…”
Section: Resultsunclassified
“…Carvalho et al (2010) verificaram a Deformação Residual Longitudinal (DRL) no diâmetro à altura do peito (DAP) do fuste de C. citriodora e E. urophylla e concluíram que a primeira espécie apresenta maior nível de tensões de crescimento.…”
Section: Introductionunclassified